2011
DOI: 10.1021/jf200623m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Edible Composite Coating Based on Gum Arabic and Chitosan on Biochemical and Physiological Responses of Banana Fruits during Cold Storage

Abstract: The composite effects of gum arabic (GA) (5, 10, 15, and 20%) and chitosan (CH) (1.0%) on the biochemical and physiological characteristics of banana fruits stored at 13 ± 1 °C and 80 ± 3% relative humidity (RH) for 28 days and afterward for 5 days at simulated marketing conditions (25 °C, 60% RH) were investigated. Significant (P ≤ 0.05) differences were observed for the entire GA plus CH treatments as compared to the control. However, the results showed that after 33 days of storage, the weight loss and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 35 publications
15
109
0
2
Order By: Relevance
“…These findings indicate that the coatings have delayed the ripening process, corroborating previous studies evaluating effects of polysaccharide coatings on fresh produce (Dang et al, 2008;Sabularse et al,2009;Duan et al, 2011;Maqbool et al, 2011). This ripening delaying effect is related to reduced respiration rates, which is expected from polysaccharidebased coatings.…”
Section: Titratable Acidity and Soluble Solidssupporting
confidence: 89%
See 1 more Smart Citation
“…These findings indicate that the coatings have delayed the ripening process, corroborating previous studies evaluating effects of polysaccharide coatings on fresh produce (Dang et al, 2008;Sabularse et al,2009;Duan et al, 2011;Maqbool et al, 2011). This ripening delaying effect is related to reduced respiration rates, which is expected from polysaccharidebased coatings.…”
Section: Titratable Acidity and Soluble Solidssupporting
confidence: 89%
“…On the other hand, polysaccharides coatings are not good moisture barriers because of their hydrophilic nature (Nisperos-Carriedo, 1994;Yang and Paulson, 2000). Indeed, the main effect of polysaccharide-based coatings on shelf-life of fruits is that of reducing respiration rates due to selective permeabilities to O 2 and CO 2 (Nisperos-Carriedo, 1994;Maqbool et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the major cause of weight loss among non-packaged samples is the migration of water from the fruit to the environment [33], and the packaging materials serve as semipermeable barriers that block oxygen, carbon dioxide, and moisture. This reduces respiration, water loss, and oxidation [34]. Since PVA has the lowest water vapor permeability, strawberries packaged with it exhibit the lowest weight loss.…”
Section: Weight Lossmentioning
confidence: 99%
“…Coatings 2017, 7, 109 [34]. Since PVA has the lowest water vapor permeability, strawberries packaged with it exhibit the lowest weight loss.…”
Section: Weight Lossmentioning
confidence: 99%
“…Decrease in firmness of fruits is due to pectinase and hydrolase enzyme activity that leads to degradation in cell structure, cell wall composition and inter and intracellular materials (Seymour et al, 1993). Inhibition of loss of firmness by edible coatings has been reported for various fruits including 10% GA in mango (Khaliq et al, 2015), 10 and 15% GA in tomato (Ali et al, 2010), combined treatment of GA and chitosin in banana (Maqbool et al, 2011). In this study, GA 5% and 10% coated fruits showed higher firmness than the control fruits and this may be due to thick coating which created a modified atmosphere around the fruit surface as a result reduced changes in pectin substances and activity of cell wall degrading enzymes.…”
Section: Physical Parametersmentioning
confidence: 49%